2007
DOI: 10.1136/vr.160.22.762
|View full text |Cite
|
Sign up to set email alerts
|

Effects of radial shockwave therapy on the limb function of dogs with hip osteoarthritis

Abstract: The objective of this study was to evaluate the effects of extracorporeal radial shock wave therapy on the hindlimb function of dogs suffering from hip osteoarthritis. Twenty-four client-owned dogs with hip osteoarthritis were investigated; 18 of them received radial shockwave therapy and six were left untreated as controls. Force plate analysis on a treadmill was used to assess the dogs' hindlimb function before treatment and four weeks after the last treatment, and the treated dogs were re-evaluated three an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 7 publications
1
50
0
9
Order By: Relevance
“…Frisbie et al [15] reported that ESWT significantly improved the degrees of lameness in horse, but no disease modifying effects as evidenced by synovial fluid analysis, synovial membrane, or cartilage. Mueller et al [16] demonstrated that ESWT significantly improved the limb function of dogs with hip osteoarthritis with the difference in ground reaction force between two limbs disappeared in four weeks after treatment. Ochiai et al [17] showed that ESWT is a useful treatment for knee OA with improvement in walking ability and reduction of calcitonin generelated peptide (CGRP) in dorsal root ganglion (DRG) neurons innervating the knee.…”
Section: Discussionmentioning
confidence: 99%
“…Frisbie et al [15] reported that ESWT significantly improved the degrees of lameness in horse, but no disease modifying effects as evidenced by synovial fluid analysis, synovial membrane, or cartilage. Mueller et al [16] demonstrated that ESWT significantly improved the limb function of dogs with hip osteoarthritis with the difference in ground reaction force between two limbs disappeared in four weeks after treatment. Ochiai et al [17] showed that ESWT is a useful treatment for knee OA with improvement in walking ability and reduction of calcitonin generelated peptide (CGRP) in dorsal root ganglion (DRG) neurons innervating the knee.…”
Section: Discussionmentioning
confidence: 99%
“…Frisbie and colleagues reported that ESWT improved the degrees of lameness in horse, but no disease modifying effects as evidenced by synovial fluid analysis, synovial membrane or cartilage 19. Mueller and colleagues demonstrated that the limb function of dogs with the difference in ground reaction force between two limbs were improved after ESWT in hip osteoarthritis 20. Ochiai et al showed that ESWT is a efficient treatment for knee OA with improvement in walking ability and the reduction of calcitonin gene-related peptide in dorsal root ganglion neurons innervating the knee 21.…”
Section: Introductionmentioning
confidence: 99%
“…ESWT has shown effectiveness in many orthopedic disorders including soft tissue tendinopathy and non-union of long bone fractures [12,13]. In addition, many studies including ours reported positive effects of ESWT in various arthritic joints in animals [14][15][16][17][18]. Our previous studies demonstrated that ESWT is chondroprotective in the initiation of OA changes of the knee [19,20], and induces regression or retardation of established OA changes of the knee in rats [21].…”
Section: Research Papermentioning
confidence: 85%